(NpOWESTI I RASSKAZY (B/ s (N~ASTX (B1s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1978)
(Nw KNIGU WHODQT RASSKAZY (B"(NrUBKA LESA(B", "(NsEWASTOPOLXSKIE RASSKAZY(B", "(Nl@CERN(B", (NPOWESTX (B"(NkAZAKI(B" (NI DRUGIE PROIZWEDENIQ l(B. (Nn(B. (NtOLSTOGO(B, (NSOZDANNYE IM W (B1850-1860 (NGODAH(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs